Implementasi Tanggung Jawab Sosial Perusahaan Melalui Pentuple Bottom Line - Nuril Badria; Naimatul Hasanah (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract This study aims to measure the achievement of business sustainability of PT. Bank Negara Indonesia Tbk through the pentuple bottom line. Pentuple bottom line, namely the reconstruction of the triple bottom line concept that helps create the implementation of corporate business sustainability, Triple bottom line consisting of profit, people and planet becomes pentuple bottom line consisting of people, profit, phenotechnology, planet, and Prophet (5P). This study is a non-positivist research, namely the postmodernist paradigm with the imaginary dialogue research method. The results of this study are the pentuple bottom line as a measure of the success of fulfilling social responsibility at PT. Bank Negara Indonesia Tbk. The hierarchical pyramid is a model of corporate obligations starting from people, profit, phenotechnology, planet, and prophet which are described in each stage. The first is people in the form of efforts made by BNI in providing benefits for stakeholders. Second, profit is an effort to achieve organizational performance. Third, Phenotechnology is the fact that the existence or phenomenon of information technology must be an important part of maintaining organizational survival. The four Planets are preserving the environment, nature must be strived for by BNI, and finally the Prophet is the balance of spirituality, mentality, or spirituality in the process of preserving life. Keywords: Reconstruction, Triple Bottom Line, Pentup Bottom Line Hierarchical Pyramid, Business Sustainability and Postmodernist Paradigm,